2020
DOI: 10.1039/d0ra00680g
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba leaf polysaccharide stabilized palladium nanoparticles with enhanced peroxidase-like property for the colorimetric detection of glucose

Abstract: Ginkgo biloba leaf polysaccharide stabilized palladium nanoparticles had high stability, good biocompatibility and low detection limit for glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 59 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Both Pd 91 ‐GBLP NPs and the P‐Co 3 O 4 /R‐Co 3 O 4 platform, which are fabricated via bioconjugation or hydrothermal techniques, can monitor glucose levels at a very low limit detection of 1 × 10 −6 m and 0.69 × 10 −6 m /0.32 × 10 −6 m , respectively. [ 20,23 ] Multi‐hydroxyl carbon dots (CDs) were aggregated on phenylboronic acid (PBA)‐molecular‐brush‐grafted magnetic nanoparticles (Fe 3 O 4 @APBA) to produce a novel glucose composite probe that can respond to glucose in human blood at a minimum level of 0.15 × 10 −6 m within 5 min (Figure 1C). [ 24 ] In other study, Long et al.…”
Section: Off‐body Sensors For Glucose Monitoringmentioning
confidence: 99%
“…Both Pd 91 ‐GBLP NPs and the P‐Co 3 O 4 /R‐Co 3 O 4 platform, which are fabricated via bioconjugation or hydrothermal techniques, can monitor glucose levels at a very low limit detection of 1 × 10 −6 m and 0.69 × 10 −6 m /0.32 × 10 −6 m , respectively. [ 20,23 ] Multi‐hydroxyl carbon dots (CDs) were aggregated on phenylboronic acid (PBA)‐molecular‐brush‐grafted magnetic nanoparticles (Fe 3 O 4 @APBA) to produce a novel glucose composite probe that can respond to glucose in human blood at a minimum level of 0.15 × 10 −6 m within 5 min (Figure 1C). [ 24 ] In other study, Long et al.…”
Section: Off‐body Sensors For Glucose Monitoringmentioning
confidence: 99%
“…In the following, the catalytic performance of these samples was evaluated as peroxidase mimics toward catalytic TMB oxidation. [5][6][7][8][9]12] The testing curves were obtained by monitoring the characteristic absorbance (A) at 652 nm (Figure 5). It was found that the activity follows such a sequence that FTO/TiO 2 < FTO/ TiO 2 /Cu 2 O < FTO/TiO 2 /Cu x O/CeO 2 either in the dark or under visible light irradiation.…”
Section: Catalytic Test As Peroxidase Mimicsmentioning
confidence: 99%
“…[3,4] In comparison, inorganic candidates have attracted much attention as enzyme mimics because of simple and stable spatial conformation of those artificially synthesized nanocatalysts. Since Fe 3 O 4 nanoparticles were first found with unexpected intrinsic peroxidase-like activity, which could complete the colorimetric reaction via catalytic oxidation of various peroxidase substrates in the presence of H 2 O 2 , [5] numerous kinds of inorganic catalysts have been successfully fabricated such as metal nanoparticles, [6,7] metal oxides, [8][9][10][11][12][13] carbon quantum dots, [14] metal organic frameworks, [15,16] metal organic gels, [17] and single-atom catalysts [18] to be served as high-activity enzyme mimics. These catalysts could not only be easily endowed with multiple functions, but also be adopted to meet the needs of design on various enzyme mimics for applications.…”
Section: Introductionmentioning
confidence: 99%
“…Gao and co-workers first reported that magnetic Fe 3 O 4 nanoparticles (NPs) possessed peroxidase-like activity . Besides, many other nanomaterials have been demonstrated to exhibit good peroxidase-like properties, such as Co 3 O 4 , Co 4 N nanowires, Prussian blue, graphene oxide, and noble metal nanoparticle . These nanomaterials have more flexible structures and higher chemical stability compared with HRP.…”
Section: Introductionmentioning
confidence: 99%
“…6 Besides, many other nanomaterials have been demonstrated to exhibit good peroxidase-like properties, such as Co 3 O 4 , 7 Co 4 N nanowires, 8 Prussian blue, 9 graphene oxide, 10 and noble metal nanoparticle. 11 These nanomaterials have more flexible structures and higher chemical stability compared with HRP. They are capable of catalyzing the oxidation of TMB into blue oxTMB, which have been further used to detect glucose concentration.…”
Section: Introductionmentioning
confidence: 99%